KEEFEKTIFAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION BERBANTUAN GEOGEBRA TERHADAP AKTIVITAS DAN PEMAHAMAN KONSEP PADA MATERI BANGUN RUANG SISWA KELAS IV DI SDN PESAREN 02 - Sigit Wibowo; Bagus Ardi Saputro; Achmad Buchori (STKIP Subang, 2023)
The purpose of this study was to determine the effectiveness of the realistic mathematic education approach assisted by geogebra on student activities and understanding of concepts. This type of research is quasi-experimental research with the Nonequivalent Control Group Design. The population in this study were fourth grade students at SD Gugus Diponegoro. The sample used for the experimental class was SDN Pesaren 2, the control class was SDN Pesaren 1, and the test class was SDN Sawahojo 2. Data were obtained through test instruments and the results of observing student activities. The results of the study prove that (1) the realistic math education approach assisted by geogebra is effective for the activities of fourth grade students at SDN Pesaren 2. This can be seen from the significance value in the t-test which is 0.000 <0.05, which means that there are differences in the results of observations of student activities between classes experimental and control class. The results showed that the average value of the experimental class was 85. The average observation result before treatment in the experimental class was 65, while the average observation result during treatment reached 85 with an average increase in learning outcomes (n-gain) of 0.566 with moderate criteria. (2) The realistic mathematic education approach assisted by GeoGebra is effective for understanding concepts in spatial material for fourth grade students at SDN Pesaren 2. This can be seen from the significance value on the t-test which is 0.000 <0.05, which means that there are differences in learning outcomes in aspects of conceptual ability mathematics between experimental classes and control classes. The learning results show that the average value of the experimental class is 85 with the specified KKM, which is 70, while the classical completeness is more than 75%, which is 85%. The average pretest in the experimental class was 65 while the average posttest result reached 85 with an average increase in learning outcomes (n-gain) of 0.566 with moderate criteria.